Graphene Composite Materials for Removal of Heavy Metals from Water: Progress and Prospects - Yi, Chen (International Journal of Natural Resources and Environmental Studies, 2024)
With the acceleration of the global industrialization process, heavy metal pollution has become increasingly serious. Heavy metal elements pose a grave threat to the ecological environment and human health owing to their high virulence, strong persistence, and bioaccumulation. Therefore, developing efficient and environmentally friendly water treatment technologies to remove heavy metal (HM) in water has emerged as current focus of environmental science research. Graphene has shown significant application potential in water treatment owing to its unique physical and chemical properties. In particular, graphene composites can be further improved in water treatment by combining graphene with other materials. This paper systematically combs and analyzes relevant literature in recent years and summarizes the research progress of graphene composites (GCs) in removing HMs such as lead, mercury, cadmium, chromium and arsenic from water. The application status, mechanism of action, and performance evaluation of GCs in removing HMs in water treatment are discussed in detail. Finally, the challenges and future development directions are analyzed. Valuable reference and guidance for the further development of GCs in the field of water treatment are provided.